Social Media Addiction among the Rural Youth: An AI Interpretation - Khanganbi, Thongam Victory; Priya, M (Indian Journal of Extension Education, 2024)
The impact of social media increasingly influences rural youth in India. Artificial Intelligence is a vast interdisciplinary arena with many domains, not only all the computing disciplines, but also linguistics, neuroscience, statistics, engineering, economics, control theory, and others. The study was undertaken to predict social media addiction by machine learning and to know the accuracy of the addiction level among rural youth. The data were collected through the snowball sampling method, including those using smartphones in rural Coimbatore during the COVID period (2022). A total of 128 rural youth from Coimbatore aged 18 to 24 years were selected as respondents and used naïve Bayes classifier methods to predict the addiction level on social media. 99 respondents were taken under the training set, and the remaining 29 were under the prediction sets to know the accuracy of the Byes model in predicting social media addiction levels. The study predicted its usage accuracy with social media addiction using artificial intelligence and machine learning. The majority of the rural youth were moderately addicted and there were many more causative variables to be assessed further. The naïve byes model accuracy in predicting social media addiction observed was 94.0 per cent.
Keywords: Rural youth; Artificial intelligence; Naïve byes; Prediction; Social media addiction,; Machine learning